Zircon and apatite fission-track dating of the Ampipal alkaline massif, the Nepal Lesser Himalaya - Gautam, Pitambar; Koshimizu, Satoshi (Journal of Nepal Geological Society, 1991)
Fission-track dates for the rocks of the Ampipal alkaline massif range from 2.60 0.19 Ma to 2.81 0.26 Ma for zircon and 1.58 0.17 Ma to 1.69 0.21 Ma for apatite respectively. These dates suggest uplift/erosion rates ranging from 2.00 to 2.22 mm/yr and the corresponding cooling rates of 80 to 89°C/Myr for the period between ca. 2.81 Ma and the present.